GC-MS Analysis of Bioactive Components of Feronia elephantum Correa (Rutaceae) - Muthulakshmi A, Jothibai Margret R, Mohan V.R. (Journal of Applied Pharmaceutical Science)
Feronia elephantum belongs to the family Rutaceae is well known in Indian traditional system for its traditional uses. The present investigation was carried out to determine the possible bioactive components of leaves and bark of F. elephantum using GC-MS analysis. 18 components from leaves and 14 components from bark of the above said plant were identified. The prevailing compounds in the ethanol extract of leaves of F. elephantum were 7– Norbornadienyl t-butyl ether (17.26%) , 2–isopropyl–5-methyl–1– heptanol (11.40%), 1– Octanol,2–butyl (8.47%), Phenol, 4–[2–(dimethylamino)–ethyl]– (4.56%), 2,3– Dimethylquinolin-4(1H)–one (3.58%), Ethyl iso–allocholate (1.63%). The ethanol extract of F.elephantum bark contained, 2–Propenenitrile, 3–(3.4-dimethoxyphenyl)–(60.72%) was found as major component followed by phenol, 4–(3-hydroxy-I-propenyl)-2-methoxy–(9.35%), 3-(2-NAcetyl– N-methylaminoethyl)indol (1.15%), cholesta–8,24–dine–3–ol, 4–methyl–(3a'- 4a')– (0.86%) as the major components.
Keywords: F. elephantum, wood apple, GC-MS, bioactive components.